2018
DOI: 10.1021/acs.langmuir.7b04295
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Interfacial Processes at Mini-Micro-Nano Scales Using Sessile Droplet Architecture

Abstract: Evaporating sessile functional droplets act as the fundamental building block that controls the cumulative outcome of many industrial and biological applications such as surface patterning, 3D printing, photonic crystals, and DNA sequencing, to name a few. Additionally, a drying single sessile droplet forms a high-throughput processing technique using low material volume which is especially suitable for medical diagnosis. A sessile droplet also provides an elementary platform to study and analyze fundamental i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…Previous work 17 has indeed demonstrated that the convective evaporation-induced assembly process can be strongly inuenced by convective uid particle transport, including the Marangoni ow, which arises from temperature and concentration gradients. [17][18][19][20] The self-assembled spherules organisation of bismuth nanosheets has not been reported before and demands further in-depth analysis. Importantly, the spheruleslike superstructure with porous morphology could provide highly accessible surfaces, which would be benecial for high ion transport essential for energy storage devices.…”
Section: Resultsmentioning
confidence: 94%
“…Previous work 17 has indeed demonstrated that the convective evaporation-induced assembly process can be strongly inuenced by convective uid particle transport, including the Marangoni ow, which arises from temperature and concentration gradients. [17][18][19][20] The self-assembled spherules organisation of bismuth nanosheets has not been reported before and demands further in-depth analysis. Importantly, the spheruleslike superstructure with porous morphology could provide highly accessible surfaces, which would be benecial for high ion transport essential for energy storage devices.…”
Section: Resultsmentioning
confidence: 94%
“…Sessile droplet evaporation studies are normally the smallest laboratories for the understanding of evaporation dynamics, and they can provide wide information contents for real applications in areas such as energy engineering, chemical engineering and chemistry, physics and physical chemistry, biology, biochemistry, medicine, pharmacology, and agricultural and environmental sciences . The sessile colloidal droplets can be investigated for complex drying patterns, , wetting and spreading, , flow instabilities, , and the impact of external forces on evaporation. , The vast majority of droplet evaporation studies are based on single droplet deposition onto the target substrate. The deposited droplet is normally desired to have a spherical caplike shape, which can be modeled via wettability (e.g., contact angle) and droplet height, for better mathematical modeling approaches .…”
Section: Introductionmentioning
confidence: 99%
“…1 The sessile colloidal droplets can be investigated for complex drying patterns, 2,3 wetting and spreading, 4,5 flow instabilities, 6,7 and the impact of external forces on evaporation. 8,9 The vast majority of droplet evaporation studies are based on single droplet deposition onto the target substrate. The deposited droplet is normally desired to have a spherical caplike shape, which can be modeled via wettability (e.g., contact angle) and droplet height, for better mathematical modeling approaches.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, Hegde et al demonstrably increased the natural scale of convection in evaporating droplets by a factor of ∼1000 using vapor-mediated interactions between water and ethanol. Evaporating droplets display a wide range of internal motions driven by interfacial/bulk perturbations. , This motion can segregate dispersed/dissolved matter (molecules, particles, polymers, vesicles, cells, and microorganisms) into a striking array of geometrical structures such as rings, mounds, fingers, and concentric circles, to name a few. Brutin et al have also demonstrated the use of pattern recognition techniques to identify and diagnose afflictions of human blood.…”
Section: Introductionmentioning
confidence: 99%